1995
DOI: 10.1182/blood.v86.8.3181.3181
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids inhibit apoptosis of human neutrophils

Abstract: Human neutrophils rapidly undergo apoptotic cell death. Because glucocorticoids are known to modulate an array of neutrophil functional activities as well as induce rapid apoptosis in susceptible lymphocyte populations, we have examined the effects of glucocorticoids on apoptosis in mature human neutrophils. In cultures of neutrophils maintained in vitro, the glucocorticoids, dexamethasone, 6 alpha-methylprednisolone, and hydrocortisone, inhibited the development of apoptotic morphology by 59% to 90% when asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
1
11

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(137 citation statements)
references
References 56 publications
7
118
1
11
Order By: Relevance
“…Whether hypoxia operates to suppress constitutive apoptosis of eosinophils within microenvironments such as inflamed airways, with re-oxygenation on exposure to oxygen in the airway lumen releasing these constraints is unknown, but would be consistent with mouse data where hypoxia increases peri-bronchial eosinophilia post-OVA challenge [50]. Glucocorticoids have dichotomous effects on granulocyte lifespan, promoting neutrophil survival yet inducing eosinophil apoptosis [62]. Although corticosteroids are used to modulate inflammatory cell function within environments that may be profoundly hypoxic, few studies have examined the impact of hypoxia on the effects of these agents.…”
Section: Discussionsupporting
confidence: 56%
“…Whether hypoxia operates to suppress constitutive apoptosis of eosinophils within microenvironments such as inflamed airways, with re-oxygenation on exposure to oxygen in the airway lumen releasing these constraints is unknown, but would be consistent with mouse data where hypoxia increases peri-bronchial eosinophilia post-OVA challenge [50]. Glucocorticoids have dichotomous effects on granulocyte lifespan, promoting neutrophil survival yet inducing eosinophil apoptosis [62]. Although corticosteroids are used to modulate inflammatory cell function within environments that may be profoundly hypoxic, few studies have examined the impact of hypoxia on the effects of these agents.…”
Section: Discussionsupporting
confidence: 56%
“…Increased neutrophil numbers may be a result of the inability of steroids to block NF-B-induced neutrophil activation and proliferation resulting from a strong viral stimulus or the ability of glucocorticoids to inhibit neutrophil apoptosis. Several studies have demonstrated that dexamethasone delays or even prevents neutrophil apoptosis, thus prolonging neutrophil survival and functional responsiveness (51)(52)(53)(54), due in part to the stabilization of the anti-apoptotic Mcl-1L protein (55). This, along with increased expression of neutrophil survival factors, such as granulocyte colony-stimulating factor (G-CSF) (56) and granulocyte-macrophage colony-stimulating factor (GM-CSF) (57), which are often induced during viral infections, may explain why dexamethasone-treated animals did not exhibit a more significant decrease in neutrophil numbers.…”
Section: Discussionmentioning
confidence: 99%
“…However, this effect is thought to involve the nucleotide receptor P2X7 and not FPR2/ALX. In comparison, ANXA1 has been shown to accelerate neutrophil apoptosis (Solito et al, 2003), although glucocorticoids that regulate ANXA1 production have antiapoptotic effects (Liles et al, 1995). El Kebir et al (2007) reported that SAA could stimulate concurrent activation of the ERK and PI3K/Akt signaling pathways, resulting in the phosphorylation of BCL-XL/BCL2-associated death promoter (BAD) protein at Ser112 and Ser136, respectively, thereby preventing collapse of mitochondrial transmembrane potential, cytochrome c release, and caspase-3 activation.…”
Section: Transcriptional Regulation and Anti-inflammatorymentioning
confidence: 99%